The Effects of Management Control Systems and Leadership Style on Company Performance - Fauziah Aida Fitri; Muhammad Syukur; Dian Faradiba (Australasian Accounting, Business and Finance Journal, 2024)
A management control system (MCS) is one of the tools used to evaluate performance at different organisational levels. This study employs the Levers of Control (LoC) dimension introduced by Simons in 1995, consisting of the belief system, boundary system, diagnostic control system, and interactive control system. Besides, leadership styles (transformational style and transactional style) are also believed to influence company performance. This study aims to investigate the role of MCS and leadership styles on company performance. The result finds that MCS and leadership styles have a significant positive impact on company performance. The findings also suggest that the transactional leadership style and the diagnostic control system could improve company performance.
Keywords: Management Control System (MCS); Leadership Style (LoC); Company Performance